PERAN TEKNOLOGI DIGITAL DALAM MENINGKATKAN KUALITAS DAN EFEKTIVITAS PEMBELAJARAN - Dwi Cahyani, Meliana; Nuraeni, Siti; Almira Diantika, Salwa; Farhurohman, Oman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology has brought significant changes to the learning process in the field of education. The use of digital technology in learning activities is considered capable of improving the quality and effectiveness of learning through easier access to information, interactive learning media, and more flexible learning methods. This article aims to analyze the role of digital technology in improving the quality and effectiveness of learning. The method used in this study is a literature review by examining various scientific journals, articles, and relevant references related to digital technology in education. The results of the study indicate that digital technology has a positive impact on the learning process, such as increasing student motivation, facilitating communication between teachers and students, supporting interactive learning, and improving learning outcomes. In addition, digital technology also provides convenience in accessing learning resources anytime and anywhere. However, there are several challenges in its implementation, including limited technological facilities, low digital literacy, and unequal internet access. Therefore, cooperation between teachers, schools, parents, and the government is needed to optimize the use of digital technology in education. Overall, digital technology has an important role in creating innovative, effective, and efficient learning processes in the modern era.